2013
DOI: 10.1089/end.2012.0222
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Music During Cystoscopy Decreases Anxiety, Pain, and Dissatisfaction in Patients: A Pilot Randomized Controlled Trial

Abstract: Purpose: To determine whether listening to music during cystoscopy decreases anxiety, pain, and dissatisfaction among patients and results in a more comfortable and better-tolerated procedure. Materials and Methods: Seventy male patients who underwent rigid cystoscopy between May 2011 and December 2011 were randomized into the following: no music (Group I, n = 35) or classical music during procedure (Group II, n = 35). Before cystoscopy, lidocaine gel was instilled in the urethra, and both groups viewed their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 20 publications
(23 reference statements)
3
79
2
4
Order By: Relevance
“…Calleary et al (11) proposed that the addition of nitrous oxide inhalation for men younger than 55 years who were undergoing flexible cystoscopy. The quest for pain and anxiety relief during cystoscopy continued with Yeo et al (12) reporting that listening to classical music during cystoscopy (using a rigid cystoscope) significantly reduced pain and discomfort levels. Zhang et al (13) and Somooro et al (14) observed a beneficial effect on pain level by allowing the patient to view the cystoscopy on a screen.…”
Section: Discussionmentioning
confidence: 99%
“…Calleary et al (11) proposed that the addition of nitrous oxide inhalation for men younger than 55 years who were undergoing flexible cystoscopy. The quest for pain and anxiety relief during cystoscopy continued with Yeo et al (12) reporting that listening to classical music during cystoscopy (using a rigid cystoscope) significantly reduced pain and discomfort levels. Zhang et al (13) and Somooro et al (14) observed a beneficial effect on pain level by allowing the patient to view the cystoscopy on a screen.…”
Section: Discussionmentioning
confidence: 99%
“…17 The positive effect of music on pain and anxiety in surgical procedures has been evaluated and proven by many studies. [18][19][20] It may be logical to use music in prostate biopsy to reduce anxiety by music-induced attention shift during this unwilling procedure. Tsivian et al used music and found beneficial impact on procedural anxiety and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies about feasibility of outpatient rigit cystoscopy. [7][8][9] In some studies, local anaesthetic gel maintenance time was recommended to be at least 15 minutes to minimize the pain perception and improve tolerance of the cystoscope. 10 We also used 2% lidocain gel instillation to urethra and waited 15 minutes before insertion of the rigit cystoscope to all patients as recommended.…”
Section: Discussionmentioning
confidence: 99%